Morphological Differences in the Vocal Tract Resonance Cavities of Professional Voices: A MRI-based Study - Ventura, Sandra Rua (2021)
The processes that take place during singing and acting are complex. However morphological and dynamic studies of the vocal tracts during speech have been gaining greater attention, mainly due to the rapid technical advances being made with Magnetic Resonance Imaging (MRI) and image analysis and processing techniques